3D velocity measurements in a premixed flame by tomographic PIV. (23rd April 2015) - Tokarev, M P; Sharaborin, D K; Lobasov, A S; Chikishev, L M; Dulin, V M; Markovich, D M
Abstract: Tomographic particle image velocimetry (PIV) has become a standard tool for 3D velocity measurements in non-reacting flows. However, the majority of the measurements in flows with combustion are limited to small resolved depth compared to the size of the field of view (typically 1 : 10). The limitations are associated with inhomogeneity of the volume illumination and the non-uniform flow seeding, the optical distortions and errors in the 3D calibration, and the unwanted flame luminosity. In the present work, the above constraints were overcome for the tomographic PIV experiment in a laminar axisymmetric premixed flame. The measurements were conducted for a 1 : 1 depth-to-size ratio using a system of eight CCD cameras and a 200 mJ pulsed laser. The results show that camera calibration based on the triangulation of the tracer particles in the non-reacting conditions provided reliable accuracy for the 3D image reconstruction in the flame. The modification of the tomographic reconstruction allowed a posteriori removal of unwanted bright objects, which were located outside of the region of interest but affected the reconstruction quality. This study reports on a novel experience for the instantaneous 3D velocimetry in laboratory-scale flames by using tomographic PIV.